MANAJEMEN LABA DAN KINERJA KEUANGAN PERUSAHAAN PENGAKUISISI SEBELUM DAN SETELAH MERGER - Puji Lestari, Novi (Manajemen Bisnis, 2011)
PT. Dwikarya Indonesia MandiriE-mail: novipl_biru2511@yahoo.co.idABSTRACTThe purpose of this study is to obtain empirical evidence of whether the acquirers perform earningsmanagement prior to implementation of the acquisition. This type of research is a comparative studywhich compares the financial performance before and after the company making acquisitions. Analysisof financial performance is using financial ratios, including profitability, and activity. The results ofdata analysis shows that there was no indication of earnings management before the acquisitions conductedby the acquirer with Increasing income accruals. Furthermore, the company?s financial performanceas measured by the ratio of total asset turnover, net profit margin, returns on assets after theacquisition has a difference in the negative direction. The conclusion is that the acquirers before theacquisition are not convicted of earnings management with increasing income accrual. Acquirer?s financialperformance before and after the acquisitions have a difference, but the condition of thecompany is in sound condition.Keywords: Acquisitions, earnings management, financial performance